The Definition of Bodily-Death as the Activation of the Human Psyche - Agai, Jock Matthew (Philosophy and Realistic Reflection, 2025)
Whenever an individual is declared brain-death, there is at that point no medical evidence to proof that the deceased still lives, resulting in the burial or the preservation of the corpse. With the rise of parapsychology and quantum mechanics, the evidence to proof that the human life ends at death is gradually becoming doubtable, thus the need to engage in further study that embraces both views of a possible existence after bodily-death and a non possible existence after bodily-death. This paper is a narrative -discuss regarding the interpretation of the Out-of-Body Experiences of people in connection to the study of a possible existence after bodily death. The author argued that the near-death experience can be used as an analogy or a reference-point for the study of death and this is in view of the resemblances between the near-death experience and other perceptions that are connected to brain-death. The target for this discussion is to further support an existing notion according to which there is a mystical being that exist in all human beings and the being, referred to as psyche leaves the physical body after death. The author used some references regarding the near-death experience to explain the dissociation of the psyche from the physical body. The author finally argued that, there is persona that leaves the body alongside the psyche which enables the experiencers of the near-death to be more conscious about the events surrounding their physical and otherworldly environments.